Pengaruh Gaya Kepemimpinan, Motivasi Kerja dan Kompensasi Kerja terhadap Loyalitas Karyawan Kantor Pos Daerah Istimewa Yogyakarta - M. Azhar; Didik Subiyanto; Tri Ratna Purnamarini (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to find out whether the influence of leadership style, work motivation, and the provision of work compensation on efforts to increase employee loyalty of the Special Region of Yogyakarta (DIY) Post Office. The type of research used in this study is a quantitative research approach. The research conducted sampling at the Special Region Post Office of Yogyakarta. The sampling technique is using the Nonprobability Sampling technique with a saturated sampling approach. The sample used was 56 respondents. The data collection method used a questionnaire that had been tested for validity, reliability, classical assumption test, multiple linear analysis, hypothesis test and determinism coefficient. The data was analyzed using SPSS version 25. The results of the study showed that partially the variables of leadership style had a positive and insignificant effect on the variables of employee loyalty, partially the variables of work motivation had a positive and insignificant effect on employee loyalty, and partially the work compensation had a positive and significant effect on employee loyalty. At the same time, it was shown that the variables of leadership style, work motivation, and work compensation had a positive and significant effect on the loyalty variables of employees of the Special Region of Yogyakarta Post Office.